Risk assessment of food contact materials - Otilia T Carvalho; Thomas Tietz; Sebastian Zellmer; Ingo Ebner; Stefan Merkel (EFSA Journal, 2022)
Abstract In the EU, any material or article intended to come into contact with food, which is placed on the market, has to comply with the requirements of the Regulation (EC) No 1935/2004 – the so called ‘framework regulation’ for food contact materials (FCM). FCM covers a wide range of materials, including plastics, paper, metal and glass, which contain chemicals that might migrate into food. These chemicals must not migrate into the foodstuff in quantities that could endanger human health, bring about an unacceptable change in the composition of the food, or bring about a deterioration in the organoleptic characteristics thereof. Despite of this general regulation, the safety of new and specific materials that are not covered must be assessed case‐by‐case. In addition, national authorities can set their own regulations, and in this context, the BfR sets recommendations, which are not legal norms, but represent a standard for the production of materials not subjected to any specific legislation and are well accepted by other European Commission member states according to the mutual recognition principle. The BfR Unit 74 is responsible not only to deal with chemical risk assessment of FCM but also to evaluate application dossiers to include new substances in the positive list of FCM chemicals. In the proposed EU‐FORA programme, the fellow had the opportunity to gain experience in the evaluation of toxicological data from applicant dossiers and in the methodologies of migration tests performed in the laboratories. Moreover, the fellow also made a bibliographic review on scientific literature on the migration studies from starch‐based materials.